(untitled) (Plant Tissue Culture and Biotechnology, 2024)
Direct and indirect in vitro organogenesis of Alocasia baginda ’Silver Dragon’ was investigated using explants of shoot tips, leaf tissue, and petiole segments. For direct shoot induction from shoot tips, MS medium containing 1.5 mg/l BAP was shown to be the most efficient (80%), producing a maximum of 6.60 ± 0.93 shoots/explant with 3.66 ± 0.38 cm in length. Directly induced shoots were multiplied using a 2.5 mg/l BAP enriched medium, where the number and length of shoots/culture were 11.60 ± 1.12 and 9.20 ± 1.01 cm, respectively. Shoots gradually increased in number and length during the 1st three sub-culture cycles in the similar medium combination but declined after 3rd cycle. Following the 3rd sub-culture cycle, there were 14.80 ± 0.58 shoots per culture, with a shoot length of 9.90 ± 0.63 cm. The greatest frequency of callus induction was 97.67% for leaf tissue and 86.67% for petiole segments when they were cultured on the media containing 3.0 mg/l 2,4-D. Impressive results regarding indirect shoot organogenesis (90%) with maximum shoot number/unit callus (16.20 ± 1.62) and shoot length (11.06 ± 0.97 cm) were noted upon transferring the callus onto MS medium containing 3.5 mg/l BAP and 3% sucrose. Within 10-12 days, 100% rooting was observed in half-strength of gelled MS medium containing 2.0 mg/l IBA, with an average of 15.40 ± 1.17 roots/culture. After being acclimatized in a potting mixture containing garden soil, compost, coco peat, and moss in a 2:1:1:1 ratio, A. baginda ’Silver Dragon’ exhibited a 100% survival rate. Established plantlets seem morphologically similar to mother plants and possess fully developed root and shoot systems, along with an adequate leaf number per plant. Plant Tissue Cult. & Biotech. 34(1): 35-47, 2024 (June)